THINKING ABOUT COCONUT BREEDING PROGRAMMES - Hugh C. Harries (International Coconut Community Journal, 1990)
The following text is based on coconut breeding experience in Jamaica, Thailand and Papua New Guinea, as well as on working visits to many (but by no means all) coconut growing countries. The ideas expressed are those of the author, but they have benefited from an open exchange of views with coconut breeding colleagues, research workers, extension officers, agricultural economists and others. Perhaps coconut farmers themselves have not been fully consulted, but the reason for this will be explained in the concluding section. To some extent, this article is a statement of intent concerning future coconut breeding work, particularly where serious disease and difficult growing conditions require more to be done than simply the introduction and multiplication of F, hybrids.